The effect of brand equity dimensions on repurchase intention - Ajeng Aquinia; Euis Soliha (Diponegoro International Journal of Business, 2020)
This research aims to find out the effect of brand equity dimensions (brand awareness, perceived quality, brand association, and brand loyalty) on repurchase intention. The population in this research were the consumers of Starbucks café in Semarang, Indonesia, by purposive technique sampling with the criteria that consumers have been purchase and consume Starbucks product. The data was collected by questionnaire and analyze by validity test, reliability test, and multiple analysis regression tests. Consistent with our proposed hypotheses, the results indicated that perceived quality and brand loyalty positively affect repurchase intention. However, our study suggested that brand awareness negatively affects repurchase intention while brand association not significantly affects repurchase intention.